A cross sectional study to determine the prevalence of early and advanced gastric cancer, and precursor conditions/lesions in a high risk population - Louwrens, H. D.(Hendrik Douw) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.D.) -- University of Stellenbosch, 1990.